Bridging secular and religious perspectives: Gender awareness in language learning in Indonesian higher education - Budi Waluyo; Anita; Akhirudin; Darisy Syafaah; Moh. Buny Andaru Bahy (Social Sciences and Humanities Open)
Despite extensive exploration of gender dynamics in Western education, limited understanding exists regarding Indonesia's dual system, where secular and religious frameworks uniquely shape gender perceptions. This study compared undergraduate students' gender awareness, attitudes toward equality, perceived impacts on learning, and strategies for enhancing inclusivity in language education. Using a mixed-methods approach, data were collected from 60 students, equally divided between public and Islamic universities, through surveys and interviews. Quantitative analysis revealed no significant differences in gender awareness (public mean = 3.90, Islamic mean = 4.33, t (58) = −1.56, p = 0.125) or the perceived importance of equality (public mean = 4.00, Islamic mean = 4.23, t (58) = −0.83, p = 0.412), with small to medium effect sizes (Cohen's d = 0.40, 0.21). Chi-square tests showed medium practical differences but no statistical significance in perceptions of gender's impact (χ2 (2) = 5.93, p = 0.205, Cramer's V = 0.31). Qualitative findings highlighted shared beliefs in the benefits of gender awareness, emphasizing reduced stereotypes, inclusive environments, and balanced representation in materials. These insights call for systemic reforms to promote gender inclusivity across institutional contexts.